PPARα as a Transcriptional Regulator for Detoxification of Plant Diet-Derived Unfavorable Compounds - Bunichiro Ashibe; Yu Nakajima; Yuka Fukui; Kiyoto Motojima (PPAR Research)
Plants contain potentially toxic compounds for animals and animals have developed physiological strategies to detoxify the ingested toxins during evolution. Feeding mice with various plant seeds and grains showed unexpected result that only sesame killed PPARα-null mice but not wild-type mice at all. A detailed analysis of this observation revealed that PPARα is involved in the metabolism of toxic compounds from plants as well as endobiotic substrates by inducing phase I and phase II detoxification enzymes. PPARα plays a vital role in direct or indirect activation of the relevant genes via the complex network among other xenobiotic nuclear receptors. Thus, PPARα plays its wider and more extensive role in energy metabolism from natural food intake to fat storage than previously thought.